2014
DOI: 10.1016/j.jhep.2013.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune liver disease, autoimmunity and liver transplantation

Abstract: Primary biliary cirrhosis (PBC), primary sclerosing cholangitis (PSC) and autoimmune hepatitis (AIH) represent the three major autoimmune liver diseases (AILD). PBC, PSC, and AIH are all complex disorders in that they result from the effects of multiple genes in combination with as yet unidentified environmental factors. Recent genome-wide association studies have identified numerous risk loci for PBC and PSC that host genes involved in innate or acquired immune responses. These loci may provide a clue as to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
163
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(171 citation statements)
references
References 151 publications
2
163
0
6
Order By: Relevance
“…An increased incidence of autoantibody formation, despite adjunctive immunosuppressive treatment, has been reported in patients who received OLT for autoimmune and non-autoimmune liver disease (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…An increased incidence of autoantibody formation, despite adjunctive immunosuppressive treatment, has been reported in patients who received OLT for autoimmune and non-autoimmune liver disease (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic criteria of recurrent autoimmune hepatitis (34)(35)(36) -Liver transplantation for confirmed diagnosis of autoimmune hepatitis -Elevated transaminases -Hyper-gammaglobulinemia (elevation of IgG) -Presence of autoantibodies (ANA, SMA and/or Anti-LKM1) -Compatible histopathology(interface hepatitis, portal inflammation and/or lymphoplasmacytic inflammatory infiltrates) -Response to corticosteroid -Exclusion of differential diagnostic considerations impact of rejection for recurrent AIH is not certain (5,32). Interestingly it is suggested that acute (fulminant) AIH is less likely to recur than chronic presentation following LT (5).…”
Section: Diagnosis Of Recurrent Autoimmune Hepatitis Its Risk Factormentioning
confidence: 99%
“…Importantly, there have been several publications regarding de novo hepatitis during or after interferon-based anti-HCV treatment for recurrent hepatitis C posttransplantation (67)(68)(69). However, its pathophysiology is still uncertain, and it is still controversial whether de novo AIH represents a specific type of rejection or a form of have reported recurrent AIH posttransplantation (8,32), since the first report by Neuberger et al in 1984 (33). However, there are no specific biomarkers to diagnose recurrent AIH.…”
Section: De-novo Autoimmune Hepatitismentioning
confidence: 99%
“…Nowadays, chronic hepatitis B, as a major hidden danger [1], is a threaten to human being's health, but there is a lock of effective measures and radical solutions to cure it [2,3]. This situation has an inseparable relationship with the persistent infection of HBV and the relative lag of the research of pathogenic molecular mechanism and the development and evaluation of antiviral drug, on account of the short of the susceptible cell models and animal models to HBV [4,5].…”
Section: Introductionmentioning
confidence: 99%